XIII-XIV դդ. հայ-իրանական մշակութային հարաբերությունների պատմությունից - Փոորմոհամմադի, Փարիսա (ՀՀ ԳԱԱ հրատ.)
Armenian-Iranian cultural relations in the 13th - 14th cc. are of special interest and on the basis of linguistics, literary, miniature painting, historic observations are well studied. The article deals with analyses of the tiles from the capital of Armenia Ani, Garni (settlement of urban type) and fortress Tiknouni, recovered during the archaeological excavations. Во время археологических раскопок в городе Аии, поселении городского типа Гарни и крепости Тикнуни было обнаружено большое количество изразцов, принадлежавших ко времени монгольского владычества в Армении (II пол. ХШ в. и XIV вв.).
Keywords: Հայագիտություն; Պատմություն